Determinants of Agricultural Intensification in Southwest Nigeria (2012)
Declining agricultural production in many developing countries has prompted increased use of some inputs while continuous cropping prevails. This study analysed the factors promoting different forms of agricultural intensification in southwestern Nigeria. Data collected from randomly selected farmers in selected states in southwestern Nigeria were used. Results show that farmers from Osun State have the highest indices of intensification with respect to land use intensity, fertilizer use intensity and crop diversification. The censored regression showed that lost working days, use of fertilizers, crop rotation, and having more inherited land increased land use intensity while use of organic manure, minimum tillage and poverty reduced crop diversification index. Fertilizer use intensity increased with the use of minimum tillage and household size while hired and family labour use intensity increased with household size. It was recommended that in the face of increasing land degradation, farmers’ access to fertilizer must be increased and efforts to reduce their poverty level must be promoted, among others.